Assessment of working fluids, thermal resources and cooling utilities for Organic Rankine Cycles: State-of-the-art comparison, challenges, commercial status, and future prospects. (15th January 2022) - Qyyum, Muhammad Abdul; Khan, Amjad; Ali, Sajid; Khurram, Muhammad Shahzad; Mao, Ning; Naquash, Ahmad; Noon, Adnan Aslam; He, Tianbiao; Lee, Moonyong
Graphical abstract: Highlights: Detailed assessment of Organic Rankine Cycles is presented. Mixture working fluids achieves higher thermodynamic efficiency. Biomass and solar energy are still rarely adopted as ORC's heat resources. USA and Europe have major share in ORC systems. Studies for reducing the levelized cost of electricity is needed to be carried out. Abstract: This paper presents state-of-the-art review on organic Rankine cycle (ORC) by assessing the working fluids, thermal resources, cooling utilities, and commercial status with future aspects. It is found that the mixture working fluids achieve higher thermodynamic efficiency. However, the difficulty in obtaining the optimum composition and components limits their applications. The thermal resources with different temperature ranges and cooling utilities are then assessed to investigate their effects on the thermodynamic performance of ORC. The low-temperature ORC utilizing waste heat and geothermal heat is dominant, while biomass and solar energy are still rarely adopted as ORC's heat resources. From the commercial perspective, the USA and Europe are the leaders in conversion of low-grade waste heat into useful power using ORC. Furthermore, the main challenges of ORC are: (a) selection of appropriate working fluid with suitable expander, and (b) reducing the specific cost of the small-scale ORC system to compete with the renewable energy. Finally, several future research directions are identified such as: (1) overall performance of the ORC system including its thermodynamic efficiency, stability and safety needs to be investigated with experimental studies; (2) a general methodology should be developed for the selection of working fluids; (3) studies for reducing the net present cost and levelized cost of electricity with techno-economic optimization are needed to be carried out. This study benchmarks the recent progress on ORC technology and presents an insight into the scientific problems that need to be explored to nexus low-grade heat to power in the future.